2023
DOI: 10.1108/dprg-11-2022-0139
|View full text |Cite
|
Sign up to set email alerts
|

Central bank digital currency and bank earnings management using loan loss provisions

Abstract: Purpose This paper aims to analyse the role of central bank digital currency (CBDC) in bank earnings management and focus on how CBDC activity might influence banks to engage in accrual earnings management using loan loss provisions (LLPs) and the implications for earnings quality. Design/methodology/approach The paper used conceptual discourse analysis to explain the role of CBDC in bank earnings management. Findings Banks will use accruals, such as LLPs, to manage earnings when CBDC-induced bank disinter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Governments and central banks could regulate some aspects of this market by considering the creation of their own centralized digital currencies, known as CBDCs, as described by Alonso ( 2023 et al (2023). Although some studies show that the general sentiment of the population towards these new central digital currencies is positive, there is also some resistance to their use in some sectors of the population, as described by Ozili and Nañez Alonso (2024).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Governments and central banks could regulate some aspects of this market by considering the creation of their own centralized digital currencies, known as CBDCs, as described by Alonso ( 2023 et al (2023). Although some studies show that the general sentiment of the population towards these new central digital currencies is positive, there is also some resistance to their use in some sectors of the population, as described by Ozili and Nañez Alonso (2024).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…(2023b) implemented a structural equation model with partial least squares-path modeling (PLS-PM) and questionnaire data. Ozili (2023b) undertook a literature review augmented by regression analysis on Nigerian banking sector data and Panwar and Agarwal (2023) applied a CBDC project index and a random forest model. Kim and Kwon (2023) utilized an overlapping-generations model, while Fujiki (2023b) conducted a survey with data from the Cash Alternative Survey.…”
Section: Resultsmentioning
confidence: 99%
“…However, once the rate is above the threshold, bank failure risk will increase, thereby undermining banking stability (Jun and Yeo, 2021). Ozili (2023b) investigated the role of central bank digital currency (CBDC) in bank earnings management, focusing on how CBDC activity might influence banks to engage in accrual earnings management using loan loss provisions (LLPs) and the implications for earnings quality. The author showed that banks will use loan loss provisions to manage earnings when CBDC-induced bank disintermediation leads to a reduction in bank deposits, a reduction in bank lending and a reduction in reported earnings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The author showed that banks will use loan loss provisions to manage earnings when CBDC-induced bank disintermediation leads to a reduction in bank deposits, a reduction in bank lending and a reduction in reported earnings. Bank managers will mitigate the reduction in reported earnings by lowering discretionary LLPs to increase reported earnings (Ozili, 2023b). Sarkisyan (2022) showed that CBDC will not necessarily crowd out bank deposits in economies with significant demand for currency, and non-interest-bearing CBDC will lead to an inflow of deposits caused by cash substitution.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation